Dynamic Synoptic Eddy Feedbacks Contributing to Maintenance and Propagation of Intraseasonal NAO - Ren, Hong‐Li; Zhou, Fang; Nie, Yu; Zhao, Shuo (Geophysical research letters, 2022)
This study examines the dynamic feedbacks generated from synoptic eddies that contribute to maintenance and propagation of the intraseasonal North Atlantic Oscillation (ISNAO) which has significant 20−60‐day variability and features clearly westward and slightly northward propagations. The ISNAO‐related eddy‐vorticity fluxes and induced forcing contribute the positive in‐phase feedback and upstream feedback to ISNAO. Due to the accumulated shearing effect of ISNAO zonal wind anomalies, synoptic eddy structures can be statistically changed in a zonally titling way, which forms quadrupole patterns of anomalous eddy structure and further generates meridional eddy‐vorticity fluxes by multiplying basic eddy velocity by anomalous eddy vorticity. These meridional fluxes diverge from the ISNAO pattern and the area in its west and mainly induce the eddy‐vorticity forcing pattern in phase with and upstream of ISNAO, where the in‐phase feedback maintains ISNAO and the upstream feedback with a northward shift contributes to the westward and northward propagations of ISNAO. Plain Language Summary The North Atlantic Oscillation (NAO) is a famous atmospheric circulation mode that strongly influences weather and climate worldwide. This study shows that NAO has a significant intraseasonal timescale (20−60‐day, denoted as ISNAO), which features clear westward and slight northward propagation. Our results demonstrate that synoptic eddies with a 2−8‐day timescale can contribute dynamic in‐phase and upstream feedbacks to the maintenance and propagation of ISNAO, respectively. Synoptic eddy‐vorticity fluxes and induced forcing can be organized by the ISNAO circulation and further generate positive in‐phase and upstream feedbacks to ISNAO. The mechanism can be depicted by decomposing statistical eddy structures, where the anomalous eddy structure originating from ISNAO plays a key role in producing the meridional eddy‐vorticity fluxes that diverge from the ISNAO pattern and mainly induce the eddy‐vorticity forcing pattern in phase with and upstream of ISNAO. These new results could help understand the distinct intraseasonal features and dynamic mechanisms of NAO. Key Points Intraseasonal North Atlantic Oscillation (ISNAO) owns a significant 20−60‐day timescale with clear westward and slight northward propagations The in‐phase synoptic eddy feedback maintains ISNAO, while the upstream feedback with a northward shift contributes to the ISNAO propagation The ISNAO‐organized meridional eddy‐vorticity fluxes and induced forcing mainly contribute to these positive in‐phase and upstream feedbacks